Puppet 3 beginner's guide start from scratch with the Puppet configuration management system, and learn how to fully utilize Puppet through simple, practical examples /: start from scratch with the Puppet configuration management system, and learn how to fully utilize Puppet through simple, practical examples. (2013) - Unknown
No abstract available